30.7k views
4 votes
In order to solve the equation −3x − 6 = 5, the first step is to

A. add 6 to both sides
B. divide by 5 on both sides
C. subtract 6 from both sides
D. multiply by 5 on both sides

User Tvd
by
5.1k points

2 Answers

3 votes
A,first step is always simplify one side to make it clear
User Yenchi
by
5.2k points
6 votes

-3x - 6 = 5

A) add 6 to both sides to isolate the variable on one side

-3x - 6 = 5 becomes -3x = 11

Now you can easily solve this by dividing both sides by -3

x =
(-11)/(3)

User Chue X
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.